The impact of sport-hunting on the population dynamics of an African lion population in a protected area - Loveridge, A; Searle, A; Murindagomo, F; Macdonald, D (Elsevier, 2007)
Between 1999 and 2004 we undertook an ecological study of African lions (Panthera leo) in Hwange National Park, western Zimbabwe to measure the impact of sport-hunting beyond the park on the lion population within the park, using radio-telemetry and direct observation. 34 of 62 tagged lions died during the study (of which 24 were shot by sport hunters: 13 adult males, 5 adult females, 6 sub-adult males). Sport hunters in the safari areas surrounding the park killed 72% of tagged adult males from the study area. Over 30% of all males shot were sub-adult (<4 years). Hunting off-take of male lions doubled during 2001-2003 compared to levels in the three preceding years, which caused a decline in numbers of adult males in the population (from an adult sex ratio of 1:3 to 1:6 in favour of adult females). Home ranges made vacant by removal of adult males were filled by immigration of males from the park core. Infanticide was observed when new males entered prides. The proportion of male cubs increased between 1999 and 2004, which may have occurred to compensate for high adult male mortality.